PENGARUH BUDAYA ORGANISASI, MOTIVASI, MELALUI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. JANUR KUNING KUDUS - Bramastya Soeryo Baskoro; Wahyu Hidayat; Handoyo Djoko Waluyo (Jurnal Ilmu Administrasi Bisnis, 2013)
Human Resources is one factor that has important part of employee cooperation progress. Remember the interest of Human Resources, so the company should pay attention for any factors that affect Human Resources to cooperate. Which one is culture organization and also a good motivation so that could influence the employee to work adapted by standard and override their self-interests. Meanwhile, employee who have job satisfaction will maximize their work to increase employee cooperation.             The type of this research is using explanatory research. The resulting primary data is processed by using interview that consists of research instrument such as questioner and guiding question, and for the secondary data obtained by observation. Population of this research is all of PT. Janur Kuning Kudus workers that contained of 90 employee. Sample calculated by census technique because it has a homogen population's character and fulfill the term of conditions as sample research. Data analyzed by validity test, reliability test, cross tab, correlation simple linear regrecy, double linear regrecy, co-efficient determination, significance test and path analysis model to analyze the relation of causes-conclusions that occurred to double regrecy if independent variables affect to dependent variables directly and indirectly.              For the result, there are direct influences of culture organization variable (X1) to job satisfaction variable (Y1) at about 0,504. Motivation variable (X2) affects to job satisfaction (Y1) at about 0,204. Culture organization (X1) affects employee cooperation (Y2) at about 0,216. Motivation (X2) to employee cooperation (Y2) at about 0,345. Job satisfaction variable (Y1) to employee cooperation (Y2) 32,3 percent sub. While, indirect influences about affection of culture organization variable to employee cooperation variable through job satisfaction is 0,162792. And affection of motivation variable to employee cooperation variable through job satisfaction is 0,065892.